3D-MOLECULAR SCREENING OF DIKETOPIPERAZINE DERIVATES ON Staphylococcus aureus DEHYDROSQUALENE SYNTHASE USING VINA - Santoso, Broto (Pharmacon, 2012)
Dehydrosqualene synthase enzyme has been used as protein target model for exploring docking simulation of pyrazoline analogues. One of diketopiperazine derivates that have similar structure to pyrazoline has antibacterial activity against Staphylococcus aureus (S. aureus). Vina is AutoDock- improved program that capable for molecular screening based on free-energy and binding conformation prediction between ligand and protein target. The aim of these studies is to screen diketopiperazine derivates on dehydrosqualene synthase of S. aureus using Vina. Diketopiperazine derivates, curcumin analogues, curcumin, pentagammavunon derivates (PGV-0 and PGV-1) were calculated for their geometry optimization energy using Gaussian-Density Functional Theory method. 3D-optimized ligands along with reference ligands were screened for their binding energy with dehydrosqualene synthase (2ZCO) by docking using Vina. The lowest values of binding energy were analyzed with statistic method. The results showed that top thirteen ligands of docking binding energy with receptor are diketopiperazine derivates (31%), curcumin analogues (31%), and reference ligands (38%). The new compounds of diketopiperazine derivates and curcumin analogues have better potency of binding energy than curcurmin as lead compound.Â Keywords: diketopiperazine, Vina, docking, Staphylococcus aureus, curcumin.